1975
DOI: 10.1017/s0043174500052917
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Inactivation of Glyphosate in the Soil

Abstract: In greenhouse studies, soil applications of 14C-methyl-labeled glyphosate [N-(phosphonomethyl)glycine] were not readily absorbed by corn (Zea mays L. ‘Michigan 400’) and soybean [Glycine max (L.) Merr. ‘Hark’]. However, glyphosate available to plants in sand culture was absorbed. Wheat (Triticum aestivum L. ‘Avon’) a sensitive bioassay plant, was used to detect the herbicide. Clay loam and muck soil rapidly inactivated 56 kg/ha of glyphosate. Autoclaving of the soil did not prevent the inactivation of glyphosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
3
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 1 publication
7
112
3
2
Order By: Relevance
“…On the basis of these properties, one would expect less ion exchange between glyphosate and clay minerals at either pH extreme because at very acidic conditions both clay and glyphosate would be positively charged and thus repel each other while at very alkaline conditions both (Sprankle et al, 1975a). would be negatively charged and also repelled.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of these properties, one would expect less ion exchange between glyphosate and clay minerals at either pH extreme because at very acidic conditions both clay and glyphosate would be positively charged and thus repel each other while at very alkaline conditions both (Sprankle et al, 1975a). would be negatively charged and also repelled.…”
Section: Methodsmentioning
confidence: 99%
“…This leads to reduced capacity of soils to retain glyphosate, as phosphate and glyphosate seem to compete for the same adsorption sites (de Jonge et al, 2001;Dion et al, 2001;Gimsing et al, 2004a;Gimsing et al, 2007). Sprankle et al (1975a) found that glyphosate adsorption in soil is through the phosphonic acid moiety in its phosphonate anion form, which is quite similar to phosphate adsorption in soil, even though the carboxylic group can also participate in this process. Results from Gimsing and Borggaard (2002) further confirmed that phosphate can desorb most of the adsorbed glyphosate on goethite and gibbsite; in contrast, glyphosate can desorb only a very small percentage of the adsorbed phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…PMG has been shown to be immobilized by soils and degraded by microorganisms [2][3][4][5][6]. Interaction of PMG with soils is related to the content of iron and aluminium (hydr)oxides [7,8].…”
Section: Introductionmentioning
confidence: 99%